2015
DOI: 10.1002/hep.27551
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β/Iinterleukin‐1 receptor‐associated kinase 1 inflammatory signaling contributes to persistent Gankyrin activation during hepatocarcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is a prototype of inflammation‐associated cancer. Oncoprotein Gankyrin, which mostly increases in HCC, plays a critical role in HCC development and metastasis. However, the exact mechanism of Gankyrin up‐regulation in HCC remains unclear. A Gankyrin luciferase reporter was developed to screen a potential regulator for Gankyrin from a list of proinflammatory cytokines, and interleukin (IL)‐1β was found as one of its activators. In clinical premalignant and malignant liver disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 40 publications
(75 reference statements)
0
42
0
1
Order By: Relevance
“…Given their important functions in cancer initiation and progression, methylation changes are currently being investigated as potential biomarkers for early cancer detection, and prediction of cancer progression and chemotherapeutic sensitivity. A recent study found that significant methylation changes in PSMD10, which encodes gankyrin, were more frequent in gastric carcinoma and GC with metastasis compared with normal samples, suggesting that PSMD10 may act as a tumor suppressor gene, as well as an oncogene, as previously reported [15,16]. Gankyrin was initially purified and characterized by Tanaka and coworkers as the p28 component of the regulatory subunit of the 26S proteasome, which is an ATP-dependent protease responsible for the degradation of proteins [17].…”
Section: Introductionmentioning
confidence: 66%
“…Given their important functions in cancer initiation and progression, methylation changes are currently being investigated as potential biomarkers for early cancer detection, and prediction of cancer progression and chemotherapeutic sensitivity. A recent study found that significant methylation changes in PSMD10, which encodes gankyrin, were more frequent in gastric carcinoma and GC with metastasis compared with normal samples, suggesting that PSMD10 may act as a tumor suppressor gene, as well as an oncogene, as previously reported [15,16]. Gankyrin was initially purified and characterized by Tanaka and coworkers as the p28 component of the regulatory subunit of the 26S proteasome, which is an ATP-dependent protease responsible for the degradation of proteins [17].…”
Section: Introductionmentioning
confidence: 66%
“…Recent data have demonstrated that aberrant activation of the PI3K/AKT pathway is also frequently implicated in the development of neuroblastoma and correlates with poor prognosis [31] . IL-1β is a pleiotropic pro-inflammatory cytokine, and its levels are increased in many cancers, including colon cancers [32] and hepatocarcinomas [33] . Interestingly, PI3K and IL1B are located within a hub region in the connected subnetwork that is targeted by nucif- Our results also suggested that nuciferine can directly target the neuroblastoma-or colorectal cancer-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…115 ( Figure 2) summarizes current knowledge about activation of Gankyrin in liver cancer and Gankyrin-dependent activities which contribute to development of liver cancer. The activation of Gankyrin in rodent models of carcinogenesis is mediated perhaps by two important events: de-repression of the Gankyrin promoter by reducing FXR signaling and subsequent activation by interleukin-1α/IRAK-1signaling.…”
mentioning
confidence: 99%